Os programas de assistência estudantil do ensino superior no Brasil: a experiência da UTFPR - Palavezzini, Juliana (2014)
In the Capitalist order, the political, economic and social context are mainly determined by the social transformations defined regularly by the relationship between State, Society and Market. The educational policies immediately or moderately express the political views of the State, in its different institutions. The main object of this research work is to analyze how the student aid policies have contributed to society as a way of bringing access conditions, reduction of student evasion and graduation, having as basis for my studies, the experience from Federal Technological University of Paraná Dois Vizinhos. Brazil is a country with disproportional numbers in terms of access and continuous stay on the educational system, especially in the higher education. In the democratization process of higher education, it´s necessary to create conditions that could help students stay within the system; as permanence and graduation are strongly linked with the social and economic characteristics of the population. In the last decades, Federal Government has presented through different norms and policies, proposals of expansion of the higher education, as well as student aid policies. Organized as: National Education Plan 2001/2010; Federal University Expansion and Restructuring Aid Plain; National Student Aid Plan, the Government action that has as objective the expansion of the higher education and define the policies for the higher education in Brazil. This path consists of three main stages. This research is organized into three chapters. The first presents a group of theoretical notions with the objective of guiding through the two following chapters. The discussion within the first chapter evolves on how the Bourgeois State has established itself and how the ideology of the bourgeoisie, the globalization of the capital and the flexibility of the production affects the State actions, sustaining the propositions of the social policies, particularly when it comes to education. The second chapter focuses on comprehend the actual configuration of the higher educational policies, concentrating on the actual normative nuances of the student aid programs. On the third chapter, we analyze the experience of Federal Technological University of Paraná Dois Vizinhos, and with this, tracing some considerations about the thematic of the programs. In this sense, the research aspires to investigate referring data about School evasion/permanent students, efficiency indexes and retention of the benefited students within the student aid programs of the institution.